Effect of moderate to high intensity aerobic exercise on blood pressure in Young Adults: the TEPHRA open, two-arm, parallel superiority randomized clinical trial - Williamson, W; Lewandowski, A; Huckstep, OJ; Lapidaire, W; Ooms, A; Tan, E; Mohamed, A; Alsharqi, M; Bertagnolli, M; Woodward, W; Dockerill, C; McCourt, A; et al. (Elsevier, 2022)
Background: Exercise is advised for young adults with elevated blood pressure, but no trials have investigated efficacy at this age. We aimed to determine whether aerobic exercise, self-monitoring and motivational coaching lowers blood pressure in this group.